2013
DOI: 10.3748/wjg.v19.i1.35
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal fibrosis associated with immunoglobulin G4-related disease

Abstract: Retroperitoneal fibrosis is a rare disease characterized by the development of inflammation and fibrosis in the soft tissues of the retroperitoneum and other abdominal organs. Retroperitoneal fibrosis can be of 2 types: idiopathic and secondary. The recently advocated concept and diagnostic criteria of immunoglobulin G4 (IgG4)-related disease, derived from research on autoimmune pancreatitis (AIP), has led to widespread recognition of retroperitoneal fibrosis as a condition caused by IgG4-related disease. We n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 39 publications
1
39
0
8
Order By: Relevance
“…It is reported that CT diagnosis of AIP has a positive rate up to 92%; however, our study shows that on the basis of pancreatic and bile duct lesions, the performances of ultrasound, CT, and MRI are similar. However, regarding the peripancreatic cystic ring and the specific performance of AIP, the highest rate is with CT (75%), which is also useful in evaluating the effect of therapy [21]. MRI has the highest rate in finding peripancreatic lymph nodes (53.6%) and also has a high rate in finding the capsule-like low-density rim around the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that CT diagnosis of AIP has a positive rate up to 92%; however, our study shows that on the basis of pancreatic and bile duct lesions, the performances of ultrasound, CT, and MRI are similar. However, regarding the peripancreatic cystic ring and the specific performance of AIP, the highest rate is with CT (75%), which is also useful in evaluating the effect of therapy [21]. MRI has the highest rate in finding peripancreatic lymph nodes (53.6%) and also has a high rate in finding the capsule-like low-density rim around the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare disease characterized by the development of inflammation and fibrosis in the soft tissues of the retroperitoneum and other abdominal organs. There will be a series of clinical manifestions once the fibro‐inflammatory tissue encases the abdominal aorta, iliac arteries and urinary duct . RPF is generally divided into two types: idiopathic RPF (IRPF) and secondary RPF.…”
Section: Introductionmentioning
confidence: 99%
“…IgG4-RD has been reported in 31%-59% of patients with idiopathic retroperitoneal fibrosis. 82 Many patients are asymptomatic and the diagnosis is made incidentally, during imaging. Systemic symptoms, back pain, or obstructive symptoms from involvement of ureters or inferior vena cava can occur.…”
Section: Non-gastrointestinal Tract Manifestationsmentioning
confidence: 99%